An exploratory case study: early career elementary teacher perceptions of adverse childhood experiences and classroom behavior - Sherman, Madeline (My University, 2024)
This dissertation examines the lived experiences of six early-career educators as they confront their district-assigned duties and the profound effects of Adverse Childhood Experiences (ACEs) within public elementary classrooms. Through an integrated analysis of teacher experiences and social-emotional learning (SEL), this research employs a four-pillar conceptual framework to investigate how elementary teachers navigate their beliefs, rapport-building strategies, motivations, and cultural awareness while supporting students facing extreme adversity. Informed by the theoretical foundations of Bandura (1986), CASEL (2023), Maslow (1943), Gorski (2019), Ladson-Billings (1995), and Gay (2000), the study addresses the complex challenges educators encounter in fostering emotional regulation and social-emotional development in high-needs educational environments. The four-pillar framework provides a comprehensive lens for understanding trauma-informed education’s critical dimensions. The first pillar focuses on educators’ beliefs and decision-making, emphasizing how personal reflections and biases inform pedagogical practices. The second pillar examines the transformative potential of SEL, underscoring the importance of building meaningful educator-student relationships while addressing the emotional labor teachers endure in managing both student and personal emotional triggers. The third pillar studies the motivational influences that sustain educators’ commitment to student well-being, even in the face of compassion fatigue and emotional exhaustion. The fourth pillar addresses cultural competence, exploring how teachers’ lived experiences and implicit biases shape their ability to create inclusive and equitable learning environments. Findings suggest that while early-career elementary educators are highly motivated to support their students, they often lack sufficient preparation and institutional support to manage their roles' significant cognitive and emotional demands. The study also highlights that cultural awareness and equity are essential to ensure trauma-informed practices do not inadvertently reinforce biases or perpetuate inequalities. Integrating the author’s narrative of overcoming childhood trauma, this research bridges personal experience with scholarly inquiry, offering a nuanced perspective on the challenges of emotional regulation faced by both students and teachers. The dissertation advocates for greater acknowledgment of the emotional labor required for elementary educators to work daily with trauma-affected students. The close interaction between educators and students necessitates continuous emotional engagement, with teachers tasked with academic instruction and managing the emotional well-being of their students and themselves. The study concludes with actionable recommendations to enhance teacher education programs, focusing on SEL, trauma-informed practices, and cultural awareness better to equip educators for the complexities of contemporary classrooms. By addressing these critical gaps, this research contributes to the advancement of more equitable and trauma-responsive educational opportunities, promoting environments that meet diverse student needs while supporting teachers' professional growth and emotional resilience.
Keywords: Adverse Childhood Experiences (ACEs); Cultural awareness; Early-career educators; Elementary education; Emotional regulation; Social-emotional learning (SEL); Sustainable practices; Teacher preparation; Trauma-informed education